03.02 Evaluation of anti-inflammatory effects of steroids and arthritis-related biotherapies in an in vitro co-culture model with immune cells and synoviocytes. (1st March 2017) - Noack, Mélissa; Ndongo-Thiam, Ndiémé; Miossec, Pierre
Abstract : Background: During rheumatoid arthritis (RA), steroids and biotherapies are two different ways to diminish inflammation, by reducing cytokine production and they are used alone and combined. Their efficacy has been established in clinical trials but their differential effects at the cellular level are less documented. The aim was to study these cellular effects using an in vitro model with synoviocytes interacting with peripheral blood mononuclear cells (PBMC) to reproduce the interactions in the RA synovium. Materials and Methods: Activated-PBMC were co-cultured with RA synoviocytes during 48 hour. A dose-response of methylprednisolone (MP) was tested and different biotherapies (Infliximab, Etanercept, Adalimumab, Tocilizumab, Abatacept and Rituximab) were added alone or in combination with MP. Cytokine production (IL-17, IL-6, IL-1β, IFN-γ and IL-10) was measured by ELISA. Results: Addition of MP to co-cultures inhibited the production of pro-inflammatory cytokines, IL17, IL-6, IL-1β and IFN-γ, but also the anti-inflammatory IL-10 secretion. The lower doses of MP were mostly as efficient as higher doses. The response to the biotherapies alone was treatment-dependent and the inhibitory effect was obtained with the lower dose. IL-17 production was inhibited only by Tocilizumab (p = 0.004 ) while IL-6 was decreased only by Infliximab (p ≤ 0.002 ). IL-1β level was affected in all conditions (p ≤ 0.03 ). IFN-γ production was mainly decreased by Infliximab (p = 0.004 ), and IL-10 by Infliximab and Tocilizumab (p ≤ 0.004 ). The combination MP and biotherapies, even at low doses did not induce an additional effect on the inhibition of pro-inflammatory cytokine production. Further, the addition of a biotherapy seemed to reduce the effect of MP alone. Nevertheless, the combination MP and biotherapies induced a higher IL-10 secretion than MP alone, mainly with Rituximab. Conclusion: Steroids inhibited the secretion of all cytokines, and low doses were as potent. A global inhibitory effect of all biotherapies was observed but with differences between treatments depending on their mechanism of action. MP and biotherapy combination did not enhance the inhibitory effect on pro-inflammatory cytokines but could have a beneficial effect by increasing IL-10 production.